The Influence of Managerial Ownership, Board of Commissioners Proportion, Auditing Committee Independence, Sales Growth, Company Size To Return of Equity (ROE) of State Owned Enterprises Which is Listed in The Indonesian Sharia Stock Index 2011-2014Period - Nisful Laila; Idzal Dwi Nantyah; Puji Sucia Sukmaningrum (AFEBI Islamic Finance and Economic Review, 2017)
The aim of this study was to determine the effect of good corporate governance, growth of sales, and firm size on ROE of State Owned Enterprises which hare listed on the Indonesian Stock Exchange in the 2011-2014 period. The method used is the quantitative method with panel data regression techniques. The data used are secondary data by collecting annual financial data statements of State Owned Enterprises which hare listed on the Indonesian Stock Exchange in the 2011-2014 period.Panel data regression conduction showed that managerial ownership (X1) has a negative and significant impact on ROE, the proportion of commissioners has a positive and significant impact on ROE (X2), the independence of audit committee (X3)has a negative and significant impact on ROE, growth of sales (X4 )has a positive and significant impact on ROE, firm size (X5) has a positive and significant impact on ROE as well as managerial ownership, the proportion of commissioners, the independence of audit committee, growth of sales, and firm size simultaneously affect the ROE of State Owned Enterprises in the 2011-2014 period.Keywords: Firm Size, Growth of Sales, Managerial Ownership, Return On Equity (ROE), The Proportion of Board Commissioners, The Independence of Audit Committee